2013 SA Heart Congress report - Hugo-Hamman, Christopher (SA Heart Journal, 2017)
The 6th World Congress of Paediatric Cardiology and Cardiac Surgery held in Cape Town in February was hosted by the South African Heart Association and organised by the Paediatric Cardiac Society of South Africa.